Answer:
Line 4
Step-by-step explanation:
The initial expression is:
12x - 19 = -4(3x - 9) - 15
The mistake was made on line 4, the correct steps to solve the expression are:
![\begin{gathered} 12x-19=-4(3x-9)-15 \\ 12x-19=-12x+36-15 \\ 12x-19=-12x+21 \\ 24x-19=21 \\ 24x-19\textcolor{#FF7968}{+19}=21\textcolor{#FF7968}{+19} \\ \textcolor{#FF7968}{24x=40} \\ x=(40)/(24)=(5)/(3) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/div2ivehjh5nz9gfjd1iij6and8gxk9v7n.png)
Because on line 4 they subtract 19 from the right side and the correct step is to add 19 to the right side.